2010
DOI: 10.2478/v10105-010-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

Regional Concentration and Specialisation in Agricultural Activities in EU-9 Regions (1950-2000)

Abstract: Both traditional (von Thünen) and modern (Hayami & Ruttan, Krugman) theories on land use suggest that productions with a high value added per unit of land tend to be located near urban centres. In this article it is tested to what extent these theoretical findings are confirmed by empirical data on agricultural land use and production for the EU-9. The focus is not only on the degree of concentration and specialisation, but also on their development over time. Growth and decline of agricultural pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…From a study on regional concentration and specialization of agricultural activities (van Leeuwen et al 2010) it appears that land-intensive, high yielding products do indeed tend to be produced in more urbanized regions. In this study long-term developments in various types of agricultural production are related to a number of socio-economic variables in order to explore regional trends in agricultural specialization between 1950 and 2000.…”
Section: Specialization In Agricultural Activities Relatedmentioning
confidence: 99%
See 1 more Smart Citation
“…From a study on regional concentration and specialization of agricultural activities (van Leeuwen et al 2010) it appears that land-intensive, high yielding products do indeed tend to be produced in more urbanized regions. In this study long-term developments in various types of agricultural production are related to a number of socio-economic variables in order to explore regional trends in agricultural specialization between 1950 and 2000.…”
Section: Specialization In Agricultural Activities Relatedmentioning
confidence: 99%
“…They are part of the labour market and, according to earlier research, in particular small local firms employ local labour (from the town and its direct hinterland) ( van Leeuwen and Nijkamp 2006). They are part of the labour market and, according to earlier research, in particular small local firms employ local labour (from the town and its direct hinterland) ( van Leeuwen and Nijkamp 2006).…”
Section: Town Actorsmentioning
confidence: 99%
“…In addition, these concentration patterns intensified during the 50 years under study. Apart from the concentration of intensive agriculture in urban regions, Van Leeuwen et al (2010a) also found that urban areas tend to be more specialized in those kinds of activities; not only can most pig breeding activities be found near cities, it also is one of the main agricultural activities in those areas. 1 On the other hand, the specialization level in dairy cattle appeared to be very similar in rural, intermediate and urban regions.…”
Section: Rural Areas and Agriculturementioning
confidence: 99%
“…Van Leeuwen et al (2010a) looked at how the level of concentration and specialization in agricultural production differs between urban and rural regions. They focus on 79 EU-9 regions in the period 1950-2000 in which they found that, in line with theories of Von Thünen (1826) and Losch (1954), for example, land-intensive and highyielding products are more often produced in the vicinity of cities.…”
Section: Rural Areas and Agriculturementioning
confidence: 99%
“…The truth is that a more common exploration of trend topics in different relations on the level of individual countries or group of countries (Renski, 2010;Otsuka, Goto and Sueyoshi, 2010;Barta, Czirfusz and Kukely, 2008;Cheshire, 2008) would advisedly be carried out parallel to economic research into specific problems focusing on continents/supra-regions (Venables, 2010;Leeuwen, Strijker and Terluin, 2010;Kraftova and Kraft, 2008).…”
Section: Introductionmentioning
confidence: 99%